PEMANFAATAN TEKS BACAAN SATUA BALI DALAM MENUMBUHKAN BUDAYA LITERASI DAN PEMBENTUKAN KARAKTER PADA SISWA SEKOLAH DASAR - I KADEK MUSTIKA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
The main problems encountered in education, especially in primary schools is the low interest in reading and the number of deviant behavior as a manifestation of bad character of students. In some of the results of research on reading interests, Indonesia ranks below countries in the world. So also with the problem of moral degradation, many behaviors such as violence, theft, rape and others that reflect not maximal character education among children and adolescents. To that end, efforts should be made pengintesifan increased interest in reading and character education. Satua Bali is an interesting read so as to stimulate students' interest in reading and ultimately foster a culture of literacy. Satua also contains a lot of character values so it is suitable to be reading by elementary school students.